2008
DOI: 10.1007/s12028-008-9048-0
|View full text |Cite
|
Sign up to set email alerts
|

Milrinone as a Rescue Therapy for Symptomatic Refractory Cerebral Vasospasm in Aneurysmal Subarachnoid Hemorrhage

Abstract: Intra-arterial Milrinone infusion seems to be a safe and effective treatment for patients who develop refractory symptomatic cerebral vasospasm following aneurysmal subarachnoid hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 30 publications
1
19
0
1
Order By: Relevance
“…Based on previously published data [16][17][18][19], patients are also administered intravenous milrinone, a phosphodiesterase III inhibitor, initially as a bolus of 0.05-0.1 mg/kg followed by an intravenous infusion titrated stepwise to a maximum of 1.5 lg/kg/min according to clinical response. Those who do not improve despite maximal medical therapy undergo angiography and assessment for possible endovascular therapy.…”
Section: Management Of DCImentioning
confidence: 99%
“…Based on previously published data [16][17][18][19], patients are also administered intravenous milrinone, a phosphodiesterase III inhibitor, initially as a bolus of 0.05-0.1 mg/kg followed by an intravenous infusion titrated stepwise to a maximum of 1.5 lg/kg/min according to clinical response. Those who do not improve despite maximal medical therapy undergo angiography and assessment for possible endovascular therapy.…”
Section: Management Of DCImentioning
confidence: 99%
“…Milrinone is an inhibitor of phosphodiesterase III, with positive inotropic and vasodilatory effects . Although intra‐arterial milrinone contributes to the reduction of VSP, this usually requires concomitant use of angiography .…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral vasospasm is a main cause of morbidity and mortality following aneurysmal SAH and contributes to delayed cerebral ischemia (DCI). 1 VSP occurs around the fourth day after SAH and usually peaks between seven and ten days. 1 Moreover, this condition is a persistent state of vasoconstriction, which is present in 70% of the patients who survive the first 24 hours after SAH.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two studies have also shown that IA milrinone appears to be safe and effective in the treatment of SAH-induced vasospasm [103,104]. Fraticelli et al [103] studied the effects of IA milrinone (8-24 mg) followed by intravenous milrinone infusion in 22 patients with cerebral vasospasm.…”
Section: Endovascular Therapy In Sah-induced Cerebral Vasospasmmentioning
confidence: 99%